2018
DOI: 10.21776/ub.jpacr.2018.007.02.374
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling of Tabat Barito (Ficus deltoidea) Using UPLC-QTOF-MS/MS

Abstract: Tabat Barito (Ficus deltoidea) is known as a plant that has potency as an antioxidant because containing a significant phenolic compound. In this study, we performed metabolite profiling on F. deltoidea leaves by UPLC-QTOF-MS/MS to identify its phenolic compounds. Extraction by maceration and ultrasonication techniques with methanol (MM and UM) and ethanol (ME and UE) were used to extract the F. deltoidea metabolites. About 70 metabolites were identified by using UPLC-QTOF-MS/MS in negative ion mode. The amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Ficus deltoidea Jack is a plant belonging to the Moraceae family, it is widespread in Southeast Asia, including Indonesia. 1,2 Rural communities in Kalimantan utilize Ficus deltoidea Jack leaves as a medicinal plant for the treatment of variety of diseases. 3 The plant has been scientifically proven to possess numerous biological activities, including antioxidant, anti-inflammatory, antimicrobial, antihypertensive, and antidiabetic activiries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ficus deltoidea Jack is a plant belonging to the Moraceae family, it is widespread in Southeast Asia, including Indonesia. 1,2 Rural communities in Kalimantan utilize Ficus deltoidea Jack leaves as a medicinal plant for the treatment of variety of diseases. 3 The plant has been scientifically proven to possess numerous biological activities, including antioxidant, anti-inflammatory, antimicrobial, antihypertensive, and antidiabetic activiries.…”
Section: Introductionmentioning
confidence: 99%
“…3 The plant has been scientifically proven to possess numerous biological activities, including antioxidant, anti-inflammatory, antimicrobial, antihypertensive, and antidiabetic activiries. 1,2,3 Phytochemical investigation has revealed that Ficus deltoidea Jack leaves contain alkaloids, phenolics, flavonoids, and steroids at concentrations of 154.31 mg/mL, 99.689 mg/mL, 62.917 mg/mL, and 49.036 mg/mL, respectively. 4 Due to its antibacterial activity, Ficus deltoidea Jack leaves have been used as mouthwash as it has been found to possess both bactericidal and bacteriostatic effects on harmful oral microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…14 Although several metabolite profiling analyzes have been carried out on several plants, metabolite profiling analysis of the active fraction of F. deltoidea on Candida has not been reported. Secondary metabolite compounds have been reported successfully isolated from F. deltoidea, among others: flavonoid compounds such as epigallocatechin, epicatechin, catechin, afzelechin, epiafzelechin, apigenin, luteolin, vitexin and isovitexin, 15 epi-lupeol, moretenol 16 which of all the compounds that have been isolated have never been reported to have activity against Candida. F. deltoidea scientific data about antifungal, especially against Candida albicans are still rarely found.…”
Section: Introductionmentioning
confidence: 99%